2019
DOI: 10.5614/bull.geol.2019.3.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Biostratigrafi dan Analisis Perubahan Kedalaman Termoklin Di Lepas Pantai Barat Daya Sumba Sejak Pleistosen Akhir Berdasarkan Kumpulan Foraminifera Planktonik

Abstract: Sari-Foraminifera merupakan mikrofauna/mikrofosil yang sering diaplikasikan dalam geologi terutama untuk analisis biostratigrafi dan paleoekologi. Wilayah lepas pantai barat daya Sumba sangat dipengaruhi oleh pergantian muson barat lautmuson tenggara dan berada di dekat salah satu jalur keluar ITF yaitu Selat Ombai-Laut Sawu yang akirnya berperan besar dalam membentuk kondisi ekologinya. Penelitian ini bertujuan untuk membuat biozonasi dan analisis salah satu parameter ekologi yaitu kedalaman termoklin di wila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Vertically, changes in the abundance and diversity of planktonic foraminifera may reflect changes in depth and time (Schiebel & Hemleben, 2017). Therefore, information about the marine ecological conditions by identifying planktonic foraminifera vertically is very important (Ardi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Vertically, changes in the abundance and diversity of planktonic foraminifera may reflect changes in depth and time (Schiebel & Hemleben, 2017). Therefore, information about the marine ecological conditions by identifying planktonic foraminifera vertically is very important (Ardi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several downcore studies have been carried out in the Indonesian waters (Figure 1), which is that, MD98-2162 (Visser et al, 2003), MD98-2170 (Stott et al, 2004), MD98-2165 (Levi et al, 2007), MD01-2378 (Xu et al, 2008), MD01-2390 (Steinke et al, 2008), SO139-74 KL (Lückge et al, 2009), GeoB 10038-4, GeoB 10029-4 (Mohtadi et al, 2010), 13GGC (Linsley et al, 2010), SHI9034 (Ding et al, 2013), MD10-3339 (Gustiantini et al, 2015), GEOB10043-3 (Setiawan et al, 2015), SO184-10043 (Li et al, 2016), BS-36 (Zuraida et al, 2017), BS-24 (Li et al, 2018), ST-13 (Damanik et al, 2019), STA3 (Hendrizan et al, 2019), OS-07 (Damanik et al, 2020a, b), and ST-08 (Ardi et al, 2019(Ardi et al, , 2020. However, only a few studies have identified the abundance and diversity of vertical planktonic foraminifera distribution to determine the marine ecological conditions (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations